The trend of climate and runoff changes in the Ba river basin - Hang, Phan Thi Thanh (Vietnam Journal of Earth Sciences, 2014)
A warming planet and changing climate will alter the distribution, volume, timing and type of rainfall, and will modifythe distribution and timing of run-off. Many regions around the world show that climate change is having an overall netnegative impact on water resources and freshwater ecosystems. The impact of climate change on local dischargevariability is considered in the Ba river basin. Ba river basin is the largest basin of the South Central region, located inthe four provinces of Kon Tum, Gia Lai, Dak Lak and Phu Yen, with a catchment area of 13,900 km2.This research applied the Mann-Kendall model to calculate and evaluate the trend of climate and runoff changes inthe Ba river basin. The result of calculation showed the increase of temperature over the Ba basin except the minimumtemperature at An Khe station. In the central of the basin - the dry area - the rainfall tends to decrease while that in thelower area tends to increase. The maximum daily rainfall tends to decrease in almost of the meteorological stationsexcept for the An Khe station. The annual runoff in the Ba river basin tends to increase whereas the maximum river flowtends to decline. The minimum river flow tends to decrease in the lower and increase in the upper area. In particulaly,the maximum and minimum sediments tend to increase in the Ba river basin.ReferencesPhan Thi Thanh Hang, Kengo Sunada,Satoru Oishi, Yasushi Sakamoto, 2010. Climate change and impacts on runoff in the Kone River Basin, Central Vietnam. Proceedings of the Fifth Conference of Asia Pacific Association of Hydrology and Water Resources. pp 221-227.Phan Thi Thanh Hang, Kengo Sunada, Satoru Oishi, Yasushi Sakamoto, 2010. River discharge in the Kone River Basin (CentralVietnam) under climate change by applying the BTOPMC distributed hydrological model. Journalof Water and Climate change. Vol. 4. pp 1-11.Kendall, M.G., 1975. Rank correlation methods, 4th ed. Charles Griffin, London.Wang, G. Q., and Coauthors, 2013. Simulating the Impact of Climate Change onRunoff in a Typical River Catchment of the LoessPlateau, China. J. Hydrometeor, 14, 1553-1561.Wang, H., Chen, Y., Li, W., Deng, H., 2013:Runoff Responses to Climate change in Aridregion of Nortwestern China during 1960-2010.Chin. Gegra. Sci. vol. 23 No.3, pp.286-300.Bộ Tài nguyên và Môi trường, 2012. Kịch bản biến đổi khí hậu và nước biển dâng.ICCP, 2008. Climate change and water. ICCP technical paper VI. 200pp.